TRANSPORTATION CONTROLS AND THE SPATIAL STRUCTURE OF URBAN AREAS - Coldstein, G S; Moses, Leon N. (American Economic Review, 1975)
The long-run effects on cities of changes in the cost of moving people are examined. Two kinds of policies are compared: those that increase the cost of travel by car, and those that improve the quality or reduce the price of public transportation. The paper argues that the former are likely to reduce auto travel more quickly. However, these policies are also more likely to cause the economies of central cities to decline more rapidly than they would otherwise. A policy of improving and subsidizing public transportation would tend to slow their rate of decline. So far as the economies of central cities are concerned, there is a set of measures that appears to be most damaging. These are the ones that increase the cost of auto travel to central cities or their core areas relative to the cost of auto travel elsewhere in standard metropolitan statistical areas. Reductions in the supply of downtown parking, special taxes on such parking, tolls to the downtown areas, are examples of such measures.